Pengaruh Lingkungan Kerja Fisik, Stres Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Desa Sulangai Kecamatan Petang Kabupaten Badung - Prami Dewi, Ida Ayu Gede; Sadiartha, A.A.Ngr. Gede; Astawa, I Putu Putra (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The problem formulation and study's goals are to ascertain how and what impact the physical workspace, workplace stress, and employee motivation have on workers' productivity. The Sulangai Village Office is the study's location, and 45 respondents made up the sample. Quantitative research is the method used. The following methods of data analysis are employed: Validity Test, Reliability, Classical Assumptions, Multiple Linear Regression, Coefficient of Determination, t test, and F test. According to the study's findings, the physical work environment has a significant positive impact on employee performance, work stress has a significant negative impact on employee performance, and motivation has a significant positive impact on employee performance. These three factors all have a significant impact on employee performance. Employee performance is significantly influenced by independent variables by a factor of 77%.